HUBUNGAN KERJASAMA DAN IMBALAN DENGAN KINERJA PEMEGANG PROGRAM PENANGGULANGAN PENYAKIT DI KOTA BALIKPAPAN - Ratno Adrianto (Jurnal Ilmiah Manuntung, 2015)
Various activities have been implemented in the prevention and control of disease in the city of Balikpapan, but based on the Health Profile 2012 field program is known that the achievement of disease control and environmental sanitation is still not maximal. This corresponds to an increase in cases of environment-linked diseases such as DBD, tuberculosis, diarrhea, ISPA and pneumonia each year. The quality of programperformance officer holder is a factor that affects the extent of success in achieving thehealth programs that have been established.The purpose of this study was to determine the relationship between co-operation, in return, infrastructure and support superior to the performance of holders of Disease Prevention program in the city of Balikpapan. This type of research is analytic surveywith cross sectional approach. The population in this study were all employees of the holder of health programs in 27 health centers with a total sampling Balikpapan 54 people. The method used is the analysis of univariate and bivariate.The results showed no significant relationship between co-operation with the performance of the holder of the eradication program (ρ value 0.002), and betweenrewards to the performance of the holder of the eradication program (ρ value 0.027).Suggestions to increase cooperation and support employers through training soft skillsand personality, as well as leadership training management organizations, as well as considering pemberiaan remuneration policy. Thus achieving the health program can be run according to plan.